THE ROLE OF GESTURES IN SHAPING THE INTERPRETATION OF SPEECH ACTS IN COMICS - Mutiara Pratama Putri; Ajar Pradika Ananta Tur; Arini Sabrina (University of Kuningan, 2024)
The importance of this study resides in its contribution to comprehending the complex connection between speech and gestures in influencing the interpretation of speech acts. The findings have implications for enhancing communication tactics in digital comics and other types of discourse. The successful integration of verbal and nonverbal cues is vital for transmitting meaning efficiently. Using a descriptive qualitative design, the primary data for this research consists of the conversations said by the characters in the comic. In addition, the photos depicting the gestures of each character serve as the corroborating data in this study. In order to get the data, the researcher employs the observation method, utilizing three distinct techniques: tapping, non-participatory observation, and note-taking. In addition, the researcher employs a data analysis technique specific to qualitative research in order to analyze the data. Ultimately, the interaction between verbal and nonverbal signals is crucial for comprehending the intended significance of speech acts. Gesture has a vital part in influencing the understanding of speech acts, and it is essential to take into account both verbal and nonverbal signals for successful communication